The Origin of Ping-Pong Diplomacy - Itoh, M. author. aut Link
XXII, 244 p.
Keywords: Why and how did Japan Table Tennis Association President Goto Koji invite China to participate in the World Table Tennis Championships in Nagoya, Japan, in 1971 (the Nagoya World's)? Against strong opposition at home and abroad, Goto Koji created a stage for Premier Zhou Enlai to launch Ping-Pong Diplomacy, which changed world history forever.